Social Determinants of Health Factors for Gene–Environment COVID‐19 Research: Challenges and Opportunities. Issue 2 (9th March 2022) - Phuong, Jimmy; Riches, Naomi O.; Madlock‐Brown, Charisse; Duran, Deborah; Calzoni, Luca; Espinoza, Juan C.; Datta, Gora; Kavuluru, Ramakanth; Weiskopf, Nicole G.; Ward‐Caviness, Cavin K.; Lin, Asiyah Yu
Abstract: The characteristics of a person's health status are often guided by how they live, grow, learn, their genetics, as well as their access to health care. Yet, all too often, studies examining the relationship between social determinants of health (behavioral, sociocultural, and physical environmental factors), the role of demographics, and health outcomes poorly represent these relationships, leading to misinterpretations, limited study reproducibility, and datasets with limited representativeness and secondary research use capacity. This is a profound hurdle in what questions can or cannot be rigorously studied about COVID‐19. In practice, gene–environment interactions studies have paved the way for including these factors into research. Similarly, our understanding of social determinants of health continues to expand with diverse data collection modalities as health systems, patients, and community health engagement aim to fill the knowledge gaps toward promoting health and wellness. Here, a conceptual framework is proposed, adapted from the population health framework, socioecological model, and causal modeling in gene–environment interaction studies to integrate the core constructs from each domain with practical considerations needed for multidisciplinary science. Abstract : Adapted from the population health framework, socioecological model, and causal modeling in gene–environment interactions, this paper proposes a conceptual framework coined as GxSDoH to represent the interactions between social determinants of health (behavioral, sociocultural, and physical environmental factors) and health outcomes. The framework integrates core constructs from each domain with practical and scale considerations for multidisciplinary COVID‐19 studies.